Diseño y construcción de máquina dobladora de tubos con accionamiento eléctrico para la empresa ISEK S.A.S. de Tunja. (2021)
he ISEK S.A.S company is responsible for the manufacture of all types of metal products, mainly the bending and cutting of metal tubes. The objective of this project is to design and build a tube bending machine with electric drive for use by the aforementioned company, in order to reduce the time it takes to manufacture curves in galvanized sheet, a process that is currently being carried out.